1993
DOI: 10.1172/jci116226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cellular defects of insulin action in type 2 (non-insulin-dependent) diabetes mellitus.

Abstract: IntroductionSeven non-insulin-dependent diabetes mellitus (NIDDM) patients participated in three clamp studies performed with 13-3HI-and [U-14CIglucose and indirect calorimetry: study I, euglycemic (5.2±0.1 mM) insulin (269±39 pM) clamp; study II, hyperglycemic (14.9±1.2 mM) insulin (259±19 pM) clamp; study III, euglycemic (5.5±0.3 mM) hyperinsulinemic (1650±529 pM) clamp. Seven control subjects received a euglycemic (5.1±0.2 mM) insulin (258±24 pM) clamp. Glycolysis and glucose oxidation were quantitated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
110
2
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(123 citation statements)
references
References 49 publications
9
110
2
1
Order By: Relevance
“…In both groups insulin concentrations were in the range known to suppress hepatic glucose production, including amino acids-derived gluconeogenesis. 32,33 On the other hand, hyperglycaemia is also known to contribute to the decline of hepatic glucose production, although with mechanisms still poorly understood. 34 Whether the more pronounced decline in plasma amino acids observed during period A of our study, as compared with the basal period, was entirely due to hyperinsulinaemia or to the combination of hyperinsulinaemia and hyperglycaemia cannot be easily understood.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups insulin concentrations were in the range known to suppress hepatic glucose production, including amino acids-derived gluconeogenesis. 32,33 On the other hand, hyperglycaemia is also known to contribute to the decline of hepatic glucose production, although with mechanisms still poorly understood. 34 Whether the more pronounced decline in plasma amino acids observed during period A of our study, as compared with the basal period, was entirely due to hyperinsulinaemia or to the combination of hyperinsulinaemia and hyperglycaemia cannot be easily understood.…”
Section: Discussionmentioning
confidence: 99%
“…In the diabetic condition, fasting hyperglycaemia provides a compensatory mechanism to maintain glucose metabolism relatively normal in the face of insulin deficiency and/or insulin resistance [8,9,12,25,33]. However, the mass action effect of glucose appears to be greater in normal than in diabetic subjects [8,9,12,25,33], suggesting the existence of a 'glucose resistance'.…”
Section: Discussionmentioning
confidence: 99%
“…Soskin and Levine in 1937 were the first to study the relationship between the blood glucose level and glucose utilization in pancreatectomized diabetic dogs and suggested that hyperglycaemia provided a compensatory mechanism to maintain normal rates of tissue glucose uptake in the presence of insulin deficiency [11]. We, as well as others, have demonstrated that in both NIDDM and IDDM individuals hyperglycaemia serves a compensatory role to offset the insulin resistance and maintain a normal rate of insulin-mediated glucose disposal [7,8,[12][13][14][15]. Despite the important role of hyperglycaemia in the maintenance of glucose homeostasis in diabetic individuals, few studies have examined the effect of hyperglycaemia on glucose utilization, and these have yielded conflicting results [16][17][18][19].…”
mentioning
confidence: 96%
“…To more reliably estimate the contribution of defects in glucose oxidation and storage to decreases in whole body glucose disposal, the fraction of glucose oxidation which is either insulin-independent or not affected by insulin resistance, needs to be estimated. One possibility is to determine glucose oxidation in the basal state, and consider this rate to represent non-insulin-dependent glucose oxidation [63,64]. This approach has two limitations.…”
Section: Control Iddm Subjectsmentioning
confidence: 99%
“…First, a small proportion of basal glucose oxidation is insulin-dependent [65], and second, the presence of insulin-sensitive glucose oxidation, which is not influenced by insulin resistance will be neglected. Even so, by subtracting basal glucose oxidation from glucose oxidation during hyperinsulinaemia, Del Prato et al [63] found that the percent of glucose oxidized and stored of total glucose disposal was similar between patients with NIDDM and control subjects. The best way theoretically is to measure glucose oxidation directly using local indirect calorimetry across muscle tissue, which is the quantitatively most important location for insulin-stimulated glucose utilization [54].…”
Section: Control Iddm Subjectsmentioning
confidence: 99%